Irreconcilable Differences: Critical Feminism, Learning at Work, and HRD - Sharon L. Howell; Vicki K. Carter; Fred M. Schied (Adult Education Research Conference, 1999)
This study explored the contradictions among critical feminist theory, Human Resource Development, and the reality of women's experiences. Missing from the HRD literature, with its managerial focus, is the centrality of workers', particularly women's experiences of HRD and the gendered nature of work itself.